Longitudinal associations of movement behaviours with body composition and physical fitness from 4 to 9 years of age: structural equation and mediation analysis with compositional data - Jairo H. Migueles; Christine Delisle Nyström; Dorothea Dumuid; Marja H. Leppänen; Pontus Henriksson; Marie Löf (BMC, 2023)
Abstract Background The associations of movement behaviours (physical activity [PA], sedentary behaviour [SB], and sleep) with body composition and physical fitness from pre-school to childhood, as well as the direction of the associations, could provide important information for healthy lifestyle promotion in children. This study investigated the longitudinal and bidirectional associations of movement behaviours with body composition and physical fitness measured at 4 and 9 years of age. Methods This longitudinal study included baseline (n = 315, 4.5 [SD = 0.1] years) and follow-up data (n = 231, 9.6 [SD = 0.1] years) from the MINISTOP study. Movement behaviours were measured for 7 days using wrist-worn accelerometers, body composition with air-displacement plethysmography, and physical fitness with the ALPHA health-related fitness test battery. Cross-lagged panel models and mediation analyses were performed in combination with compositional data analysis. Results We did not observe direct associations of the movement behaviours at 4 years with either body composition or physical fitness at 9 years (all P > 0.05). However, fat mass index at 4 years was negatively associated with vigorous PA (VPA), relative to remaining behaviours (VPA, β = − 0.22, P = 0.002) and light PA (LPA), relative to SB and sleep (β = − 0.19, P = 0.016) at 9 years. VPA (relative to remaining), moderate PA (MPA) (relative to LPA, SB, and sleep), and SB (relative to sleep) tracked from 4 to 9 years (all β ≥ 0.17, all P < 0.002), and these behaviours shared variance with fat mass index (all|β| ≥ 0.19, all P < 0.019), and aerobic, motor, and muscular fitness (all|β| ≥ 0.19, all P < 0.014) at 9 years. Mediation analysis suggested that the tracking of VPA (relative to remaining behaviours) from 4 to 9 years was negatively associated with fat mass index (β ≥ − 0.45, P = 0.012), and positively with aerobic fitness at 9 years (β ≥ 1.64, P = 0.016). Conclusion PA and SB tracked from the pre-school years into childhood. Fat mass index at 4 years of age was negatively associated with VPA (relative to remaining behaviours) and LPA (relative to SB and sleep) at 9 years of age. The tracking of VPA was associated with lower fat mass index and higher aerobic fitness at 9 years of age. These findings suggest that higher levels of VPA in pre-school age, if maintained throughout childhood, may support the development of healthy body composition and aerobic fitness levels in later childhood.